A Uniform Conspiracy Mindset or Differentiated Reactions to Specific Conspiracy Beliefs? Evidence From Latent Profile Analyses. Issue 1 (19th October 2021) - Frenken, Marius; Imhoff, Roland
Conspiracy theories arise for virtually any public event (e.g., pandemics, assassinations, disasters). In light of positively correlated endorsements of such beliefs, many have pointed to a more general mindset behind this. Others have argued against this notion of a consistent mindset. Applying Latent Profile Analyses, we examine the evidence for either uniform or differentiated response patterns to various items in five studies (reanalyzed datasets, total N = 7877). Overall, the results speak strongly to uniform reactions that could be summarized as a general mindset, but also revealed important qualifications. First, small parts of the samples show more differentiated patterns in relation to extraterrestrial cover-up narratives ( Studies 2 to 4 ) or contradictory theories ( Study 5 ). Second, indicators dealing with the general suppression of relevant information in the public were among the items with the highest approval ratings across all classes. One discussed implication is that existing scales are useful tools to measure conspiracy mindsets. Another implication is that the average endorsement of any conspiracy theory is a function of both the respondents' conspiracy mindset and the item's psychometric difficulty, strongly suggesting interpreting item endorsement only in relative terms, but refraining from interpreting a high agreement as an absolute number.